2019
DOI: 10.1016/j.heliyon.2019.e02202
|View full text |Cite
|
Sign up to set email alerts
|

A study on the impact of fire crackers on airborne microflora during diwali

Abstract: Diwali is celebrated widely in Asian countries, with a custom of firing crackers. Crackers pollute the environment with noise, particulate matter and chemicals. There are reports on the variation of particulates during firing crackers but none on airborne microbes. The present study was conducted to know the impact of fire crackers on airborne microflora. The air samples were collected 3 days prior to Diwali, on Diwali and 3 days after Diwali during the year 2017 at 15 different areas in Chennai, India. Anders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Besides, the 24-h mean particle concentration at all locations during the pre-Diwali, Diwali, and post-Diwali days were significantly higher than NAAQS. Health impacts to the exposed population during the festival days have extensively been studied by several researchers (Prakash et al 2019 ; Beig et al 2013 ; Sarkar et al 2010 ; Ravindra et al 2003 ). Studies conducted in India on Diwali festival estimated an increase in ratios of cardiovascular and respiratory mortalities to those of normal days by up to ~ 3.5 (Beig et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the 24-h mean particle concentration at all locations during the pre-Diwali, Diwali, and post-Diwali days were significantly higher than NAAQS. Health impacts to the exposed population during the festival days have extensively been studied by several researchers (Prakash et al 2019 ; Beig et al 2013 ; Sarkar et al 2010 ; Ravindra et al 2003 ). Studies conducted in India on Diwali festival estimated an increase in ratios of cardiovascular and respiratory mortalities to those of normal days by up to ~ 3.5 (Beig et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many epidemiological studies have established the fact that increased particulate concentration is directly associated with hospitalization and mortality for respiratory and cardiovascular diseases and a decrease in lung function (Prakash et al 2019 ; Beig et al 2013 ; Perrino et al 2011 ). Also, the fine particulate pollution typically acts as a medium to disseminate the viruses and keep them in the atmosphere for a certain period and is also a cause for the pandemic (Comunian et al 2020 ; Zhou et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study demonstrated that the firework emission can produce serious health effects in mammalian cell and lungs irrespective of the particle size [30]. A study revealed that there is a decrease in air borne bacteria due to exposure of toxic chemicals on Diwali day [31]. Mariselvam et al conducted a health survey in the year 2017 and stated that about 45% of urban people were facing problem with eye irritation during the Diwali festivals [32].…”
Section: Results Of Previous Research For Firework Pollution and Heal...mentioning
confidence: 99%
“…Beig et al, (2013) evaluated Diwali related health effects using AP method to nd that 'relative risk (RR)' is more associated with the smaller, PM2.5 range particulates. There are many studies (Ghei and Sane 2018; Mukherjee et al 2018) that dealt with quanti cation of pollution enhancement due to re crackers on Diwali day and their health impacts due to increase in airborne micro ora (Udaya Prakash et al 2019).…”
Section: Introductionmentioning
confidence: 99%